2005
DOI: 10.1039/b411325j
|View full text |Cite
|
Sign up to set email alerts
|

Clean osmium-catalyzed asymmetric dihydroxylation of olefins in ionic liquids and supercritical CO2 product recovery

Abstract: The combination of ionic liquids (ILs) as solvents in the asymmetric Sharpless dihydroxylation (AD) with the use of scCO(2) in the separation process allows a very simple, efficient, clean and robust system for the reuse of the AD catalytic system, which also does not need the use of organic solvents either for the reaction or for the separation of products and allows the isolation of the diol, in high yield and enantiomeric excess and basically without contamination with osmium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…The model substrate in these studies was 1-hexene. In this work, we performed a series of experiments of AD were selected as potential candidates for further experiments, on the basis of previous study of the AD reaction in ILs for a range of aryl and alkyl-olefins [21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The model substrate in these studies was 1-hexene. In this work, we performed a series of experiments of AD were selected as potential candidates for further experiments, on the basis of previous study of the AD reaction in ILs for a range of aryl and alkyl-olefins [21].…”
Section: Resultsmentioning
confidence: 99%
“…In line with our ongoing interest in the development of new ILs [30], their application in separation technology [27c,31], and their use as an efficient reaction medium for catalyst immobilization [19a,c,32], and encouraged by the results obtained for the AD reaction on the model substrate 1-hexene [21], we applied this methodology to the important substrate methyl transcinnamate 1. The importance of this substrate lies in the fact that it allows for the preparation of the diol 2, a known efficient precursor for the synthesis of the taxol side chain 3 (Scheme 1).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This reaction has been performed on methyl E-cinnamic acid esters in ionic liquids, with the product recovery involving extraction with scCO 2 . [42,43] 6 giving the best results (88 % yield, < 0.05 % Os). The reaction and extraction were repeated 6 times, with addition of fresh substrate and oxidant each time.…”
Section: Other Asymmetric Catalytic Reactions In Supercritical Fluidsmentioning
confidence: 90%
“…[84] Subsequently, the same team has also studied their K 2 OsO 2 (OH) 4 -L* catalytic sys- [86] Recently, with the team of Nunes da Ponte who has studied different mixtures of ILs under high pressures of CO 2 , [87] Afonso et al have shown the efficiency of the use of scCO 2 in the separation process, allowing a better recyclability of the catalyst/IL system. [88] As for Songs team, it observed that the use of OsO 4 with (DHQ) 2 (57)]. [85] These asymmetric dihydroxylation processes, in particular the effect of the ligand structure on recyclability, have subsequently been studied by Sheldon et al [89] ð57Þ S. Zhang et al have mono-quaternized Songs ligand to obtain (QN þ )(QN)PHAL (Scheme 18).…”
Section: Dihydroxylationmentioning
confidence: 98%